The effectiveness of using instagram content to promote charitable crowdfunding campaign - Putra, Setiawan Mandala; Kusumasondjaja, Sony (Jurnal Ekonomi dan Bisnis, 2022)
Crowdfunding has emerged as a new form of financing. The purpose of this paper is to investigate the differences in empathy and trust of potential donors when they find an Instagram content promoting charitable crowdfunding campaign using different types of message appeals and different levels of argument quality. This study is aimed to test whether issue involvement moderates the effect of empathy and trust on the intention to donate. To do so, an experimental design was conducted involving 180 undergraduate students from one university in Indonesia. The participants were Instagram active users who were familiar about crowdfunding. Result show Instagram content using altruistic appeal will generate stronger empathy compared to those using egoistic appeal, but different message appeals did not result significant difference on trust. Different levels of argument quality also generated different empathy and trust. Content with strong argument tends to produce stronger empathy and trust than those with weak argument. The empathy and trust of potential donors can have a positive impact on their intention to donate. In this study, it was found that issue involvement did not moderate the effect of empathy and trust on the potential donors' intention to donate.